Simvastatin and nanofibrous poly(L-lactic acid) scaffolds to promote the odontogenic potential of dental pulp cells in an inflammatory environment - Soares, Diana G. [UNESP] (2018)
In this study, we investigated the anti-inflammatory, odontogenic and pro-angiogenic effects of integrating simvastatin and nanofibrous poly(L-lactic acid) (NF-PLLA) scaffolds on dental pulp cells (DPCs). Highly porous NF-PLLA scaffolds that mimic the nanofibrous architecture of extracellular matrix were first fabricated, then seeded with human DPCs and cultured with 0.1 mu M simvastatin and/or 10 mu g/mL pro inflammatory stimulator lipopolysaccharide (LPS). The gene expression of pro-inflammatory mediators (TNF-alpha, IL-1 beta and MMP-9 mRNA) and odontoblastic markers (ALP activity, calcium content, DSPP, DMP-1 and BMP-2 mRNA) were quantified after long-term culture in vitro. In addition, we evaluated the scaffold's pro-angiogenic potential after 24 h of in vitro co-culture with endothelial cells. Finally, we assessed the combined effects of simvastatin and NF-PLLA scaffolds in vivo using a subcutaneous implantation mouse model. The in vitro studies demonstrated that, compared with the DPC/NF-PLLA scaf-fold constructs cultured only with pro-inflammatory stimulator LPS, adding simvastatin significantly repress the expression of pro-inflammatory mediators. Treating LPS+DPC/NF-PLLA constructs with simvastatin also reverted the negative effects of LPS on expression of odontoblastic markers in vitro and in vivo. Western blot analysis demonstrated that these effects were related to a reduction in NFkBp65 phosphorylation and up-regulation of PPAR gamma expression, as well as to increased phosphorylation of pERK1/2 and pSmad1, mediated by simvastatin on LPS-stimulated DPCs. The DPC/NF-PLLA constructs treated with LPS/simvastatin also led to an increase in vessel-like structures, correlated with increased VEGF expression in both DPSCs and endothelial cells. Therefore, the combination of low dosage simvastatin and NF-PLLA scaffolds appears to be a promising strategy for dentin regeneration with inflamed dental pulp tissue, by minimizing the inflammatory reaction and increasing the regenerative potential of resident stem cells. Statement of Significance The regeneration potential of stem cells is dependent on their microenvironment. In this study, we investigated the effect of the microenvironment of dental pulp stem cells (DPSCs), including 3D structure of a macroporous and nanofibrous scaffold, the inflammatory stimulus lipopolysaccharide (LPS) and a biological molecule simvastatin, on their regenerative potential of mineralized dentin tissue. The results demonstrated that LPS upregulated inflammatory mediators and suppressed the odontogenic potential of DPSCs. Known as a lipid-lowing agent, simvastatin was excitingly found to repress the expression of pro-inflammatory mediators, up-regulate odontoblastic markers, and exert a pro-angiogenic effect on endothelial cells, resulting in enhanced vascularization and mineralized dentin tissue regeneration in a biomimetic 3D tissue engineering scaffold. This novel finding is significant for the fields of stem cells, inflammation and dental tissue regeneration. (C) 2017 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.